April Fool’s Day - Bannwart, Shanti Elke (Ars Medica, 2014)
The room is soaked in the grayish powdered light of a fading moon. By rolling my left eye from one side in an arc upwards and then back downwards. I decipher the objects around me. i repeat this tiny oblong circle several times, delighting in the ability to move around in this room by moving my eye, the only part of my body that follows my will and intention.